2021
DOI: 10.1038/s41598-021-03561-9
|View full text |Cite
|
Sign up to set email alerts
|

Effect of histone H4 tail on nucleosome stability and internucleosomal interactions

Abstract: Chromatin structure is dictated by nucleosome assembly and internucleosomal interactions. The tight wrapping of nucleosomes inhibits gene expression, but modifications to histone tails modulate chromatin structure, allowing for proper genetic function. The histone H4 tail is thought to play a large role in regulating chromatin structure. Here we investigated the structure of nucleosomes assembled with a tail-truncated H4 histone using Atomic Force Microscopy. We assembled tail-truncated H4 nucleosomes on DNA t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
31
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

6
0

Authors

Journals

citations
Cited by 12 publications
(32 citation statements)
references
References 36 publications
1
31
0
Order By: Relevance
“…CENP-A nucleosomes on other substrates were found more commonly in varied and over wrapped states, as seen in Figure 6 . Previous studies have indicated the importance of internucleosomal interactions in canonical nucleosomes to their positioning and stability [ 24 , 25 ], and this effect may be even more critical at the centromere. The improved stability of CENP-A nucleosomes on α-satellite DNA could provide a synergistic effect with internucleosomal interactions, allowing this region to withstand the forces the centromere is subjected to during cell division [ 30 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…CENP-A nucleosomes on other substrates were found more commonly in varied and over wrapped states, as seen in Figure 6 . Previous studies have indicated the importance of internucleosomal interactions in canonical nucleosomes to their positioning and stability [ 24 , 25 ], and this effect may be even more critical at the centromere. The improved stability of CENP-A nucleosomes on α-satellite DNA could provide a synergistic effect with internucleosomal interactions, allowing this region to withstand the forces the centromere is subjected to during cell division [ 30 ].…”
Section: Discussionmentioning
confidence: 99%
“…The goal of this study was to reveal nanoscale structural characteristics of nucleosomes assembled on the α-satellite sequence. We utilized Atomic Force Microscopy (AFM) with the capability to characterize nucleosomes on the single molecule level with nanometer resolution to address this issue [ 22 , 23 , 24 , 25 , 26 ]. We assembled CENP-A nucleosomes on three different substrates: a substrate containing an α-satellite motif, a substrate containing non-specific DNA and nucleosomes assembled on the Widom 601 positioning motif to determine whether CENP-A has distinguishing structural characteristics between α-satellite and other DNA sequences.…”
Section: Introductionmentioning
confidence: 99%
“…Note however, that histone tails not only bridge the nucleosomes, but also can hinder the formation of the tight internucleosomal contacts. We have recently shown that truncation of histone H4 can shift the internucleosomal distance for the dinucleosome constructs to smaller distances (Stormberg, Vemulapalli, et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…5. Previous studies have indicated the importance of internucleosomal interactions in canonical nucleosomes to their positioning and stability (24,25), and this effect may be even more critical at the centromere. The improved stability of CENP-A nucleosomes on α-satellite DNA could provide a synergistic effect with internucleosomal interactions, allowing this region to withstand the forces the centromere is subjected to during cell division (34).…”
Section: Discussionmentioning
confidence: 99%
“…The goal of this study was to reveal nanoscale structural characteristics of nucleosomes assembled on the α-satellite sequence. We utilized Atomic Force Microscopy (AFM) with the capability to characterize nucleosomes on the single molecule level with nanometer resolution to address this issue (22)(23)(24)(25)(26). We assembled CENP-A nucleosomes on three different substrates: a substrate containing an α-satellite motif, a substrate containing non-specific DNA and nucleosomes assembled on the Widom 601 positioning motif to determine whether or not CENP-A has distinguishing structural characteristics between α-satellite and other DNA sequences.…”
Section: Introductionmentioning
confidence: 99%